NEGOTIATING THE INTEGRATION OF ISLAMIC STUDIES WITHIN HEALTH SCIENCES EDUCATION: INSIGHTS FROM CURRICULUM DESIGN AND CLASSROOM PRACTICE - Agus Warcham; Abudin Nata; Nirwan Syafrin; Budi Handrianto; Irma Nurbaeti (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study seeks to understand how the integration of Islamic studies is negotiated in health sciences education by examining the interaction between curricular intentions and teaching practices in everyday learning contexts.The study adopts a qualitative case study design. Data were generated through semi structured interviews with lecturers and academic managers, supported by analysis of curriculum documents and direct observation of classroom activities. The collected data were examined through thematic interpretation to capture how integrative decisions are formed and enacted.The findings show that while Islamic perspectives are formally acknowledged within curriculum frameworks, their realization in classroom instruction varies considerably. Lecturers interpret integrative goals in diverse ways, balancing religious values with professional competencies, disciplinary standards, and practical teaching constraints. As a result, integration emerges through selective emphasis, adaptation, and compromise rather than uniform application.The study concludes that integrating Islamic studies into health sciences education is best understood as a negotiated and evolving process. Sustainable integration requires institutional strategies that recognize pedagogical diversity and support lecturers in aligning religious perspectives with professional learning objectives.